Differences in Response to Creatine Supplementation in Women Depending on the Menstrual Cycle Phase: A Narrative Review - Myślicka, Wiktoria; Veyeunik, Valery; Chrobak, Agata; Kacynel, Ewa; Zhukava, Lizaveta; Volkava, Darya; Sakovich, Volha; Alansi, Abdulrahman; Weng, Kai-Chiun; Bessmylna, Kateryna; et al. (Quality in Sport, 2026)
Background. Creatine monohydrate is a widely used ergogenic supplement not subject to the rigorous pharmaceutical standardization or regulatory requirements applied to medicinal products. The majority of research has been conducted in male populations, limiting the validity of direct extrapolation to women. Women have inherently lower creatine stores, and cyclical fluctuations in estradiol and progesterone modulate endogenous creatine synthesis and post-exercise recovery - a domain insufficiently explored in the literature. Aim. To synthesize available evidence on the influence of menstrual cycle phase on women’s response to creatine supplementation, encompassing physical performance, recovery, and mood. Materials and methods. A literature search was conducted using PubMed, Scopus, and Google Scholar. Data from meta-analyses, systematic reviews, observational studies, and RCTs on creatine metabolism and female physiology were synthesized. Results. Women exhibit lower endogenous creatine stores and distinct creatine kinase kinetics compared to men. The luteal phase is associated with increased protein catabolism, reduced exercise tolerance, and impaired recovery. Creatine supplementation reduces the fatigue index during the luteal phase and demonstrates potential for mood improvement during the premenstrual phase. Conclusion. The available evidence suggests that the luteal phase may represent a period of increased creatine demand, during which creatine supplementation could potentially provide greater performance and recovery benefits in women. However, dedicated randomized controlled trials are required to confirm this hypothesis.